ISIS DALAM DISKURSUS PEMBENTUKAN NEGARA BANGSA - Laode Muhammad Fathun (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2015)
The development of international phenomenon relations that afflicts all areas of life changes the relation of conventional international format. The domination of the issue of war and peace becomes the main debate. The emergence of the phenomenon of globalization is changing the format in the international relations. In the debate over international relations paradigm hanaya incorporate military, economic, political as the main study. However, after emerging issues of fundamentalism asthe Western theory of Islamist groups is not so keen in doing analysis. Secretary- General NATO Willy Claes said NATO was formed to stop the fierce-fierce missiles the Soviets Union against USA missiles. However, NATO is not set up to address the movement of fundamentalism. The emergence of fundamentalist movements in the Middle East is being real evidences the inclusion of religion in international politics.In assuming the realist never concentrated with the issue of religion in politics only plays on the nature of the human being. Liberalism is only playing in institutional norms while the constructivist place in reality is a social construction. The vacuum religion in international politics after the 30 years ended the war between Catholics and Protestants in Europe. However, it was another story when the value of Islamic fundamentalism entered in international politics into a new chapter of how Islam viewsthe relationship between the nation State. Western dominance with a democratization value certainly tends to conflict with Islamic theological values. The command from God that Islam is a religion that haq will rule the world and require that Islam came to power and sovereign political and legal basis. With the assumption that Islam is a lifesaver for man and man as God’s representative on Earth, then humans must livewith the quantity of Islamic values. ISIS is an organization in the cap as a aims to create a fundamentalist movement dawlah Islamiah or countries within the context of Islamic Universalism. They choose any strategy –violent and non violent alike- to reach this aims.Keywords: shifting issues of international relations, politics, religion andfundamentalism, ISIS, Jihad